O jednoj ljubavi izgubljenoj u prevodu (Philologia, 2021)
In this paper, the author analyses a Serbian translation of Angela Carter’s novel Love. The research has revealed numerous mistakes which are classiﬁed and clariﬁed in order to show that (and why) the translator has, on the whole, done a poor job. Therefore, it can be concluded that the translation does not do the British writer justice at all, because it is more than unsatisfactory, at times even incomprehensible. Unfortunately, the Serbian rendering also undermines the reputation of our professional literary translators, showing them in a very dim light.